SISTEM EMULSI SOSIS SINTETIS DARI GLUTEN DAN RUMPUT LAUT (Euchema cottoni) (Synthetic Sausage Emulsion System of Gluten and Seaweed) (Jurnal Teknologi Pangan, 2015)
Abstract Sausage usually use beef, but vegetarians can not consume, so that consider alternative sausage manufacture of vegetable material sausages example of gluten. Advantages of gluten was compared to beef contains no cholesterol and is relatively cheaper price. The addition of seaweed (Euchema cottoni) in the manufacture of synthetic sausage is expected to improve the quality of the sausage because physicochemical mineral (iodine) content and carrageenan in seaweed (Euchema cottoni). sausage is oil in water emulsion (o / w) which is formed from a mixture of fat and water in the colloidal protein phase as an emulsifier. Problems in the manufacture of synthetic sausage gluten and seaweed (Euchema cottoni) is produced emulsion system is not good and therefore contributes to quality sausages produced. This study aims to determine the emulsion system on synthetic sausages from gluten and seaweed on its quality. The experimental design used in this study is completely randomized design (CRD) factorial with two replications and two factors. The factor I is the addition of vegetable oil (4%, 6%, 8%, 10%) and Factor II, the addition of egg yolk (3 %, 5%, 9%, 18%). The results showed that the best treatment is the addition of vegetable oil 6% and 12% egg yolk which produces synthetic sausage criteria: water content of 46.4043%, 20.2781% protein content, fat content of 11.2442%, 35.4947% WHC , 95.7453% emulsion stability, texture and 1.5195 mm / gr.dt.nilai 268 organoleptic taste, aroma and texture 299 300.   Keywords: Sausage, emulsion, gluten, seaweed Abstrak   Sosis biasanya menggunakan daging sapi, tetapi golongan vegetarian tidak dapat mengkonsumsi , sehingga dipikirkan alternatif pembuatan sosis dari bahan nabati misalnya sosis dari gluten. .Keunggulan gluten dibandingkan dengan daging sapi adalah tidak mengandung kolesterol dan harganya relatif lebih murah. . Penambahan rumput laut (Euchema cottoni ) dalam pembuatan sosis sintetis diharapkan dapat meningkatkan kualitas fisikokimia sosis karena kandungan mineralnya (yodium) dan karagenan dalam rumput laut (Euchema cottoni ) . sosis merupakan emulsi minyak dalam air (o/w) yang terbentuk dari campuran lemak dan air dalam fase koloid dengan protein sebagai emulsifier .Permasalahan pada pembuatan sosis sintetis dari gluten dan rumput laut (Euchema cottoni) adalah sistem emulsi yang dihasilkan kurang baik sehingga berpengaruh terhadap kualitas sosis yang dihasilkan . Penelitian ini bertujuan mengetahui system emulsi pada sosis sintetis dari gluten dan rumput laut terhadap kualitasnya. Rancangan percobaan yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL) pola faktorial dengan dua faktor dan dua kali ulangan: Faktor I penambahan minyak nabati (4%, 6%, 8%, 10%) dan Faktor II penambahan kuning telur (3%, 5%, 9%, 18%). Hasil penelitian menunjukkan bahwa perlakuan terbaik adalah penambahan minyak nabati 6% dan kuning telur 12% yang menghasilkan sosis sintetis dengan kriteria : kadar air 46,4043%, kadar protein 20,2781 %, kadar lemak 11,2442 %, WHC 35,4947%, stabilitas emulsi 95,7453 %, dan tekstur 1,5195 mm/gr.dt.nilai organoleptik rasa 268 , aroma 299 dan tekstur 300.   Kata Kunci: Sosis, emulsi, gluten, rumput laut